2019
DOI: 10.3892/ol.2019.10780
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin inhibits the epithelial‑mesenchymal transition initiation in osteosarcoma cells via the p38MAPK signaling pathway

Abstract: Diosgenin is an important basic raw material for the production of steroid hormone drugs. It can be isolated and purified from a variety of traditional Chinese medicines or plants. Modern molecular biological studies have shown that diosgenin inhibits various tumor cells migration and invasion ability to varying degrees in vitro and in vivo. The aim of the present study was to observe the inhibitory effects of diosgenin on the invasive and metastatic capabilities of osteosarcoma cells and to determine the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Wnt signaling pathway is a key signal transduction pathway that induces EMT in epithelial tissues [25,26]. Recent studies by Liu et al confirmed that EMT activation can increase the invasion and metastasis ability of osteosarcoma cells, and promote the progression of osteosarcoma [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway is a key signal transduction pathway that induces EMT in epithelial tissues [25,26]. Recent studies by Liu et al confirmed that EMT activation can increase the invasion and metastasis ability of osteosarcoma cells, and promote the progression of osteosarcoma [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…it is generally believed that the eMT phenomenon only occurs in epithelial-derived cells. However, recent studies have shown that certain mesenchymal cells can also alter eMT-related protein and enhance the metastasis process (21,22). osteosarcoma (oa) is the most common bone malignant tumor of mesenchymal origin.…”
Section: Discussionmentioning
confidence: 99%
“…(47,66,67) Osteosarcoma is a kind of osteogenic malignant tumor, which has a high incidence in primary malignant bone tumors. (68) Diosgenin could inhibit the invasion and migration of osteosarcoma cells MG63 and U2OS, the proliferation of human osteosarcoma cell 1547, as well as osteosarcoma cell S180, and it could block the cell cycle in G 1 phase and induce apoptosis. (59,68,69)…”
Section: Lung Cancermentioning
confidence: 99%
“…(68) Diosgenin could inhibit the invasion and migration of osteosarcoma cells MG63 and U2OS, the proliferation of human osteosarcoma cell 1547, as well as osteosarcoma cell S180, and it could block the cell cycle in G 1 phase and induce apoptosis. (59,68,69)…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation